Myocardial Perfusion Imaging (MPI), An Overview (Cardiovascular Journal, 2010)
The clinical utility of radiotracer study of heart in nuclear cardiology must always be considered in the of context of other cardiac diagnostic procedures, including ECG, Echo, ETT,CAG and cardiac enzymes or serum cardiac protein. So one should not be a hop cardiologist.Two modalities in Nuclear Cardiology: 1).Radionuclide Angiography (RNA) or Radionuclide Ventriculography. 2).Myocardial Perfusion Imaging (MPI).Radionuclide Angiography (RNA) or Radionuclide Ventriculography: This procedure is designed to provide measurement of LVEF in patient of coronary artery disease, valvular heart disease or cardiomyopathy. In our setting we determine EF from MPI, so Radionuclide Angiography routinely not do in many centre of world including NICVD, Dhaka.Myocardial Perfusion Imaging (MPI): MPI, more specifically myocardial perfusion single photon emission computed tomography (SPECT) is a nice tool for the noninvasive assessment of myocardial perfusion, ejection fraction, wall motion, and wall thickness.Why not perform cardiac catheterization and coronary angiography in all patients suspected of having coronary artery diseases?The contrast coronary angiogram displays the anatomic extent of epicardial coronary artery disease, the severity of luminal narrowing, and the number of diseased vessels. Stress radionuclide myocardial perfusion imaging, on the other hand, displays the downstream functional consequences of epicardial coronary artery disease in the myocardium. It also may visualize the regional effects of micro vascular endothelial dysfunction and impairment of regional coronary flow reserve. Application of MPI: The diagnosis of coronary artery disease remain common application of MPI ,but it is increasingly being used for the diagnosis of acute MI, risk stratification after infarction, and assessment of viable myocardium versus scar in patients in chronic coronary artery disease. Keywords: Myocardial Perfusion Imaging (MPI); Myocardial viability; Radiopharmaceutical DOI: 10.3329/cardio.v3i1.6428Cardiovasc. j. 2010; 3(1): 55-65